THEORETICAL ASPECTS OF APPLICATION OF BUDGET AND TAX FEDERALISM IN THE RUSSIAN FEDERATION - Alexei V. Dujov (Статистика и экономика, 2016)
The idea of federalism on the state level has its continuance in forming inter-budget relations, principals and its practice. The application of tax federalism includes definition and differentiation of competence of federal centre, federal subjects and local government in determining, imposition and collection of taxes.